Prospect of aromatic grass cultivation in salt affected soils of semi-arid region in India - Basak, B. B.; Saha, Ajoy; Chinchmalatpure, Anil; Manivel, P. (Indian Farming, 2019)
Aromatic grasses have tremendous potential to rehabilitation of salt affected soil as well as generate additional income source for smalland marginal-farmers. The ecofriendly reclamation technique for salt affected soil includes three aspects: soil quality improvement, environmental sustainability as well as additional income generation for farmers.